2011
DOI: 10.1055/s-0031-1300248
|View full text |Cite
|
Sign up to set email alerts
|

Role of Guanylyl Cyclase Activation via Thiamine in Suppressing Chemically-induced Writhing in Mouse

Abstract: The possible role of L-arginine/nitric oxide (L-arginine/NO) pathway in the antinociceptive activity of thiamine (vitamin B 1 ) in p-benzoquinone-induced mouse writhing model was investigated. Thiamine (ED 50 , 0.11 mg/kg), L-arginine (50 mg/kg), N G -nitro-L-arginine methyl ester (L-NAME, 75 mg/kg) and morphine (ED 50 : 0.13 mg/kg) displayed antinociceptions following s.c. administrations (52.4 ± 5.5 %, 36.8 ± 7.7 %, 27.8 ± 11.1 %, 66.1 ± 3.5 %, respectively). However, methylene blue (MB, 40 mg/kg, s.c.) prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
2
5
2
Order By: Relevance
“…The results of the present study indicate that exogenous (s.c.) administrations of the agents which have modulatory effects on L-arginine/NO/cGMP pathway modify pyridoxine-induced antinociception in mice in contrast to our previous findings with another B complex vitamin, thiamine [24].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of the present study indicate that exogenous (s.c.) administrations of the agents which have modulatory effects on L-arginine/NO/cGMP pathway modify pyridoxine-induced antinociception in mice in contrast to our previous findings with another B complex vitamin, thiamine [24].…”
Section: Discussioncontrasting
confidence: 99%
“…It is also known that L-arginine is metabolized via the nitric oxide synthase (NOS) to form nitric oxide (NO), which is a messenger in the central and peripheral nociceptive processing individually or [18−21] and citrulline or via arginase to produce urea and Lornithine is further metabolized to polyamines by PLPinduced coenzymatic synthesis and L-proline [22,23]. We have previously shown that another B group vitamin, thiamine (vitamin B 1 ) produces antinociceptive effect by the possible involvement of a central and/or peripheral L-arginine/NO/cGMP pathway in the pbenzoquinone (PBQ)-induced abdominal constriction test in mice [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, morphine significantly reduced PBQinduced abdominal constrictions as previously shown [22,35] and the NO precursor L-arginine also significantly increased morphine-induced analgesia in contrast to findings of Bian and Bhargava [43] and Contreras et al [44]. On the other hand, our results are in agreement with those of Brignola et al [45] who suggested that the L-arginine/NO pathway modulates both the central and peripheral antinociceptive effects of morphine and this modulation seems to take place at peripheral sites.…”
Section: Discussionsupporting
confidence: 85%
“…of PBQ at a dose of 2.5 mg/kg caused abdominal constriction in all control animals. Mepyramine (ED 50 : 5.6 mg/kg) [22], morphine (ED 50 : 0.13 mg/ kg) [22], L-arginine 50 mg/kg [35] and L-NMMA (50 mg/ kg) were injected alone and in combinations s.c. half an hour before the injection of PBQ and the solutions were adjusted to make an injection volume of 0.1 ml per 10 g of mouse. The experiments were performed at room temperature (20−22°C).…”
Section: Pbq-induced Abdominal Constriction Testmentioning
confidence: 99%
See 1 more Smart Citation